Poetical Postmodern Exegesis: Paul Ricoeur and Olivier-Thomas Venard in Dialogue - Weisel, Aaron James (Verbum Vitae, 2025)
In a postmodern linguistic turn, Paul Ricoeur pays great attention to the subject and the Biblical text itself. This helpfully presents a very pristine text, one which can move and re-create the subject who encounters the text with humility. However, when it comes to Biblical exegesis specifically, Ricoeur’s method is immanentist, a historical, and unhelpfully rejects any interpretive authority. Olivier-Thomas Venard, like Ricoeur, pays great attention to the sign-character of the Bible’s language, but offers a more holistic exegesis which takes the Bible on its own terms and is metaphysically and historically grounded. In this article, I first lay out Ricoeur’s poetical exegetical project and offer interpretive and metaphysical critiques; specifically, I contend that his “distanciated” reading of the Bible and his rejection of authority fail to interpret the Bible on its own terms. I then turn to Venard, who sympathizes with Ricoeur’s subjective and linguistic turn while remaining grounded in interpretive authority, history, and providence, offering what Matthew Levering calls a “participatory exegesis.”